Hubungan Antara Efikasi Diri Dengan Quarter Life Crisis Pada Alumni Dari Tiga Perguruan Tinggi Di Kota Makassar - Jihan Fahira; Muh. Daud; Dian Novita Siswanti (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
Quarterlife crisis is an emotional crisis in the form of negative emotions in individuals in early adulthood. Negative emotions that occur can inhibit individual productivity, and even cause disturbances both physically and mentally. This study aims to determine the relationship between self-efficacy and quarter-life crisis in college alumni. The sample in this study were 115 individuals aged 22-30 years who were graduate from universities in Makassar. The research method uses quantitative methods with data collection techniques using a Likert scale, namely the QLC scale from Mutiara (2018) and the self-efficacy scale made by the researcher. The results of hypothesis testing using the Spearman Rank Correlation test showed significant results with a total of 0.00 (p < 0.05) and a correlation coefficient of -0.418. These results indicate that there is a relationship between self-efficacy and quarterlife crisis, which means Ha is accepted and H0 is rejected. It can be concluded that there is a significant relationship between self-efficacy and quarter-life crisis in college graduates in Makassar. It was found that the lower the level of self-efficacy, the higher the level of the individual's quarterlife crisis.